Practical learning through radiation physics problem solving. - Currie, H.; Lough, C.; Currie, G.; Bushong, S.; Bailey, D.L. (Radiography, 2022)
The identification of unknown radionuclides is an authentic practical activity for students that provides the foundations for clinical problem solving, especially in the storage and management of radioactive waste. As different radionuclides have different half-lives, some of which are quite long, the storage of waste material has to accommodate the longest of these. Cross contamination requires a method of identifying the radionuclide samples in a mixed sample to safely and appropriately manage disposal. Similarly, identifying a single unknown sample of a radionuclide allows correct handling and disposal. Performing a systematic investigation of the physical properties of unknown radioactive samples is a rich learning opportunity to instil understanding of important physics principles among students in nuclear medicine. This manuscript outlines an investigation developed that would allow students to identify single unknown radionuclides based on physical properties and identify the constituent radionuclides of a mixed sample using some additional mathematical curve stripping. The processes and solutions are provided with real data and this practical activity can be replicated by students generating their own data. This paper provides a template and analysis/interpretation guideline for educators and clinicians to deepen understanding of foundation physics. Enhanced and deeper understanding are a vehicle for improved problem solving in clinical and research practice.